EDUKASI MENGENAI MENINGIOMA, FAKTOR RISIKO DAN UPAYA PENANGANANNYA - Putra, Andika Fauzan; Yuliyanah, Yuliyanah; Putri, Ananda Farah Alifia Putri; Mulyawan, Bima Oriesto; Sari, Eni Endang; Hidayah, Ganjar Pratama; Ramadhan, Imam Akbar; Devita, Arleen (Jurnal Pengabdian Masyarakat Trimedika, 2024)
Meningioma is one of the most common types of benign intracranial neoplasms with a percentage of 30% of all primary brain tumors. Objective: to provide education to the public, including risk factors and treatment efforts related to meningioma. Methods: Education was carried out during a visit to the home of one of the patients in Krendang Village. The service team consists of 7 students and 1 accompanying lecturer. Home visits were carried out twice, on November 13 and 14 2023, to a 53 year old woman with chief complaint was ringing in her ears. The results of the physical examination showed blood pressure 170/90 mmHg, BMI 27.63 Kg/m2, the results of the last blood sugar level were 280 mg/dl, the results of the MRI examination concluded that there was a meningioma in the left temporal region. Results: Patient understanding regarding controlling risk factors, symptoms and signs, complications, treatment and prevention efforts for meningiomas. Conclusion: Education is an important part of comprehensive meningioma management. Family and local community support can help patients with meningioma undergo treatment to improve quality of life